A mixed methods study of early childhood providers' perceptions of the acceptability and feasibility of parenting for lifelong Health tip sheets in Ontario, Canada - Mari Dumbaugh; Susan M. Jack; Jenna Ratcliffe; Amanda Sim; Jacinda Burns; Teresa Bennett; Harriet L. MacMillan; Andrea Gonzalez (BMC, 2024)
Abstract Background Universal parenting campaigns are efficient, cost-effective and can eliminate barriers to accessing conventional, face-to-face parenting interventions. The aims of the CHAMPP4KIDS study were to assess Canadian early childhood providers' perceptions of the acceptability and feasibility of implementing a universal parenting resource, the Parenting for Lifelong Health tip sheets. Methods Using a convergent mixed method design, an online survey of providers working with families with young children in Ontario, Canada was followed by focus group discussions with a subset of providers to explore their perceptions of using the tip sheets in their professional practice. Results Providers generally perceived the tip sheets to be acceptable but had reservations with respect to the feasibility of distributing the sheets to their clients as standalone, universal parenting resources. Providers agreed the tip sheets covered topics pertinent to caregivers' concerns, offered useful strategies and, therefore, had the potential to be valuable, engaging resources for families. However, many providers said the sheets would only be effective as complementary resources to facilitated in-person sessions, especially for high-needs families. Conclusion Providers suggested that future iterations of these resources take into consideration more accessible design and formatting, literacy levels, word choice and further cultural adaptation. Insight into the nuances and potential divergence between provider perceptions of universal materials' acceptability and feasibility can help adapt materials to pre-emptively respond to potential implementation barriers, facilitate intervention fidelity and, ultimately, increase the likelihood of intervention acceptability and feasibility of both providers and caregivers.